Detection of Newcastle Disease Virus Genome from the Field Outbreaks in Poultry by Reverse Transcription – Polymerase Chain Reaction - Singh, K.; Jindal, N.; Gupta, S.L.; Gupta, A.K.; Mittal, D. (International Journal of Poultry Science, 2005)
A total of 30 field samples (27 tissue samples comprising of either trachea, lungs or brain; and 3 allantoic fluid samples) were collected from broiler chickens for detection of Newcastle disease virus (NDV) by RT-PCR. In addition, vaccine strains (F, LaSota, R2B) were taken as positive control and trachea from unvaccinated healthy bird as negative control. Newcastle disease virus (NDV) was detected in five field samples as well as in all the vaccine strains by RT-PCR. All these samples as well as vaccine strains yielded a band of 356 bp on amplification of F region of NDV. Three more field samples yielded a band of 216 bp with nested PCR, thus making total eight field samples positive for NDV. The results of the present study indicated that RT-PCR followed by nested PCR can be used to detect NDV directly from tissue samples in poultry.